2015
DOI: 10.1016/j.proeng.2015.01.143
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Emission of Ag2S Quantum Dots and their Fluorescence Quenched by Gold Nanoparticles

Abstract: The near-infrared emitting Ag 2 S quantum dots (QDs) coated with L-cysteine were prepared by one-pot aqueous synthesis at room temperature. Several characterization methods including X-ray diffraction (XRD), transmission electron microscopy (TEM), fluorescence spectrophotometer (PL) and ultraviolet -visible spectrophotometer (UV-vis) were used to characterize the structure, morphology and optical properties of the samples. The effects of gold nanoparticles on the fluorescence of Ag 2 S QDs were systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It is well known that silver sulfide exhibits quantum dots properties. Xiulan Wu et.al ( 2015 ) have shown that for spherical Ag 2 S nanoparticles of 5 nm in diameter, the maximum emission peak appears at the wavelength of ca. 750 nm, after excitation at 520 nm.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that silver sulfide exhibits quantum dots properties. Xiulan Wu et.al ( 2015 ) have shown that for spherical Ag 2 S nanoparticles of 5 nm in diameter, the maximum emission peak appears at the wavelength of ca. 750 nm, after excitation at 520 nm.…”
Section: Resultsmentioning
confidence: 99%